Shame by Any Name: The Map Is Not the Territory. Issue 1 (3rd April 2017) - Southern, Stephen
ABSTRACT: This report describes the journey from the well-established constructs of sexual addiction and compulsivity toward new directions in sexual health and optimal sexuality. Conflicting diagnoses are discussed. The ultimate destination for the field is professional consensus seeking, advocacy for effective treatment, and advancement of sexual health .